The Role of Biofertilizers in Soil Health Improvement and Sustainable Farming: A Comprehensive Review - , Keerthanan. P; , Ashoka P; , Vikas Singh; , Renam Bhargavi; , Nuthalapati Pujitha; , Thandra Anusha; , Tallam Pavani Lakshmi Hima Bindu (Archives of Current Research International, 2025)
The Role of Biofertilizers in Soil Health Improvement and Sustainable Farming. Biofertilizers have emerged as a promising alternative to chemical fertilizers, contributing to sustainable agriculture by enhancing soil fertility, improving crop productivity, and minimizing environmental degradation. These natural formulations containing beneficial microorganisms such as nitrogen-fixing bacteria, phosphate-solubilizing bacteria, potassium-mobilizing bacteria, and mycorrhizal fungi promote nutrient availability through various mechanisms, including nitrogen fixation, phosphate solubilization, potassium mobilization, and organic matter decomposition. Biofertilizers play a critical role in improving soil microbial diversity, enhancing soil structure, increasing organic matter content, and contributing to carbon sequestration. Despite their numerous advantages, several challenges hinder their widespread adoption, including limited awareness, inconsistent performance under field conditions, and inadequate regulatory frameworks. Variability in biofertilizer effectiveness due to environmental factors, carrier material selection, and poor formulation techniques remain significant barriers to their efficient utilization. Recent advancements in biofertilizer technology, including the development of multi-functional biofertilizers, genetic engineering, and microbial consortia, have shown promising results in improving their efficacy. Integrating biofertilizers with modern agricultural practices, such as precision agriculture, offers new opportunities for enhancing their performance and promoting large-scale adoption. Effective policy support, training programs, and public awareness initiatives are essential for promoting biofertilizer usage among farmers. Future research should focus on enhancing formulation techniques, conducting long-term impact studies on soil health, and establishing standardized guidelines for quality control. Addressing these challenges will ensure the successful implementation of biofertilizer technology, contributing to agricultural sustainability and environmental protection.